The Sacred Site: The Conservation Based on The Local People in Tengger Community and Its Potential as Ecotourism Activities - Purnomo Purnomo; Anggraeni In Oktaviani; Iwan Nugroho (Publisher of Widyagama University of Malang (UWG Press), 2018)
Tengger is one of the Java sub-tribes that has a belief system in the form of a life view called Kejawen. Kejawen's life is a view that is considered holistic in looking at the environment. The traditional wisdom of the Tengger community in the management of natural resources is one of the living and sustainable local wisdom in Indonesia. One of the local wisdom associated with environmental management is the existence of sacred areas as a part of environmental conservation. This research was conducted in Ngadas Village, Poncokusumo District, Malang Regency. The purpose of this study is to study the types of areas that are sacred by the Tengger community and the factors behind the existence of the area as a part of the conservation-based ecotourism. This research was conducted by interviewing the key person of the traditional leader. The interview materials in questions include the types of sacred places and the reason behind the area is sacred. The research results showed that the form of preservation of certain sacred areas has a unique ecosystem and shows the historical ties. The areas considered by the Ngadas community as sacred sites have indigenous values such as Pedanyangan, Sanggar Agung, Mbah Sedek tombs, Punden Kutungan, the mount of Bromo, the mount of Semeru, Savanna land and Bromo caldera and other sacred sites. The sacred place is highly respected by the Tengger people. Norms and values in Tengger culture incorporate with the respect for the sacred places. The existence of these sacred areas can be used as a part of environmental conservation-based ecotourism.JEL Classification: P32, Q01, Z32